Getting to Work: The Challenge of the Women Back Into Stelco Campaign - Luxton, Meg; Cormon, June (Labour/Le Travailleur, 1991)
Abstract In 1978-79, the ad hoc Women Back Into Stelco Committee launched a campaign to force Stelco management to end twenty years of sexist hiring practices. The campaign succeeded in winning public and legal recognition that Stelco had practiced discriminatory hiring and it forced Stelco to begin hiring women. This paper reviews the campaign and explores what happened when the women entered the formerly all-male workplace. It assesses the implications of such campaigns for the sex/gender division of labour the organization of work, and the politics of the women's movement and the labour movement.